ไพโรไลซิสของน้ำมันจากทะลายปาล์มเปล่าเป็นเชื้อเพลิงชีวภาพเหลวบนแมกนีเซียมออกไซด์และถ่านกัมมันต์ - ญาดา ปาลกะวงศ์ ณ อยุธยา (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The research aims to study the pyrolysis of oil from palm oil empty fruit bunch perform in a 70 ml. batch reactor over magnesium oxide and activated carbon as a catalyst. To study the parameters which affect to the liquid yield and product distribution of liquid by using 2k factorial experimental design to investigate the condition which give the highest liquid yield and product distribution like as diesel. The results shown that the optimum condition at the temperature of 430 ℃, time of reaction of 60 minutes, initial hydrogen pressure of 5 bars and using 5 wt of magnesium oxide and activated carbon gave the highest of liquid yield of 66.68 %wt, 1.73 %wt of gas and 11.59 of solid obtained. The product distribution was analyzed by simulation distillation gas chromatograph which found that the production distribution of naphtha, kerosene, diesel and log residue of 22.50 wt%, 17.50 wt%, 55.00 wt% 5.00 wt% respectively.